Combined in-silico and in-vitro experiments support acid-base equilibrium as a tool to estimate the localization depth of 4-nitrophenol within a phospholipid bilayer - Clop, Eduardo M.; Fraceto, Leonardo F. [UNESP]; Miguel, Virginia; Gastaldi, Salomé; de Paula, Eneida; Perillo, María Angélica (Elsevier, 2022)
The interaction and location of 4-nitrophenol (PNP) in biomembranes are relevant in the bioaccumulation and potentiation of the intensive toxic effects of this persistent organic pollutant. In this work, in-silico analyses predicted that, in a fluid phospholipid bilayer, the minimum energy of the protonated (PNPH) and deprotonated (PNP−) species is located within the glycerol and choline region, respectively. This was experimentally confirmed by acid-base equilibrium experiments and theory, allowing the estimation of the mean location of PNP within a bilayer region with a dielectric constant D = 50.6 compatible with the phosphate/choline moiety of egg-yolk phosphatidylcholine unilamellar (EPC) vesicles. The comparison with the D = 43.2 value obtained in Triton X-100 micelles allow predicting a mean surface potential of ψ = 25.37 mV for the EPC-water interface. Changes in the chemical shifts and longitudinal relaxation times of EPC hydrogens by 1H NMR confirm the deeper location of the PNPH within the glycerol region and at the choline region (PNP−) at higher pH. Intermolecular PNP−EPC dipolar interactions within the choline region was also demonstrated at pH 10.2 using ROESY experiments. Additional information was obtained trough 31P NMR, that detected an increase in the anisotropy at the membrane interface after insertion of PNP which probably act as a bridge between choline moieties rigidizing the crystalline structure at that spot. Concluding, here we provide experimental support to the “pH-piston hypothesis” proposed some decades ago in the pharmaceutical field, and that reinforce the importance of the environmental conditions (e.g. pH) to modulate the bioavailability of this highly toxic pollutant.
Keywords: 2D ROESY; 1H NMR; 31P NMR; Acid-base equilibrium; P-nitrophenylphosphate